Capital structure and firm's performance of property companies: evidence from Bursa Malaysia / Atiqah Batrisyia Zainalabiden - Zainalabiden, Atiqah Batrisyia (Faculty of Business Management, 2017)
The paper investigates the relationship between capital structure and firm performance. The investigations are performed by using panel data approach. A sample size of 17 listed Malaysian companies on Bursa Malaysia Berhad has been taken to analyse the relationship between leverage and firm performance. A period of 10 years from 2006-2015 data has been considered to analyse the leverage effect. The study uses two performance measures (including return on asset and Tobin’s Q as dependent variables. Capital structure is measured using long-term debt, short-term debt, total debt and growth. Size is a control variable. In this study, the capital structure is contemplated in terms debt and equity. The relationship between capital structure and firm performance has received a vast amount of attention from researchers who are trying to figure out the relationship. This is because it represents one of the most debateable issues in the field of finance. The data will be only focusing on property sector. Thus, the findings of the study would enhance the literature on capital structure and its relevant for the Malaysia listed companies in taking its capital structure decisions.